'Spirit of Dayton' -käsite Daytonin rauhansopimuksen poliittisena uudelleentulkintana - Lähteelä, Arttu (2012)
Bosnia and Herzegovina has been fragile state controlled by the international community since the Bosnian war that was ended by the Dayton Peace Agreement made in 1995. As part of the Dayton Agreement a new institution called the Office of High Representative (OHR) was established as the controlling body ensuring the peace and stability in the country. The OHR found huge difficulties in implementing the Dayton Accords, and was soon given legislative powers, as well as controversial powers to control media and to remove elected politicians from their posts in order to secure the implementation of civil aspects of the Dayton Peace Accords. These new powers given to the OHR were widely legitimized by the concept ‘Spirit of Dayton’ in order to strengthen the OHR’s mandate. However, local political actors found the new interpretation as fake and not valid, and politicized the growth of powers of the OHR by verbally attacking the concept.